China’s Impossible Trinity The Structural Challenges to the “Chinese Dream” - Lo, Chi. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
This book highlights the difficult policy choice that must ultimately be made during China's structural reform according to the theory of the Impossible Trinity, between exchange rate and monetary policy autonomy.